SEMI RING POLINOM ATAS ALJABAR MAX-PLUS - Suroto Suroto (Universitas Jenderal Soedirman, 2012)
In this paper we define polynomials over a max plus algebra. Furthermore we prove that the set of such polynomials is a semi ring.